1786 N.C. Sess. Laws 407, An Act for Raising Troops for the Protection of the Inhabitants of Davidson County, ch. 1, § 5. - (:unkn) unknown (General Publisher, 1786)
That every able bodied man who shall be enlisted into the said service, and shall furnish himself with one good rifled or smooth bored gun fit for service, one good picker, shot-bag and powder-horn, twelve good flints, one pound of good powder, and two pounds of good leaden bullets or buck shot suitable to his gun . . . [shall be provided with certain items of clothing].
--
Keywords: ARMED FORCES